Coverage in airborne backbone network - Bo ZHENG; Hengyang ZHANG; Yong LI; Wei CHENG (Tongxin xuebao)
The high-altitude long-durance unmanned aerial vehicle (HALE-UAV) equipped with directional antenna and the cuboid-shaped air corridor (AC) were taken as the study objects,and the basic idea was to extract the invariant coverage area of moving spherical cones,cylinder,as the basic component to fill AC.The general goal was to employ HALE-UAV as few as possible under the condition that the height of the cylinder was larger than that of AC.The circular and triangular orbits of HALE-UAV were analyzed in geometry respectively,and the mathematical expressions of the radius and height of the cylinder were derived.Then two coverage schemes were introduced.Through comparing the two schemes by optimization theory,the optimal coverage strategy was derived.Results show that the circular orbit is better than the triangular orbit.Moreover,the optimal solution is to employ the quasi-static floating platforms,and the suboptimal is to adopt the circular orbit of a small radius,or the triangular orbit of a small side,with a HALE-UAV on an orbit.